Brand knowledge of AIESEC in Portugal and its relationship with purchase intention - Graça, João Miguel Matos da Cruz (2021)
Nowadays, brands are increasingly playing a strategic role in non-profit organizations. Previous studies have concluded that brand knowledge influences what comes to mind when consumers think about a brand. Studies have also confirmed that brand knowledge relates to consumers’ purchase intention. However, despite the literature developments, there is a lack of understanding of those concepts in the non-profit sector. Hence, the purpose of the present study is to investigate the brand knowledge of a non-profit organization and its relationship with purchase intention. The organization selected for this study is AIESEC in Portugal. The research addresses Keller’s model (1993), in which brand knowledge is conceptualized in terms of two components: brand awareness and brand image. The study was developed by applying both qualitative and quantitative methods. The qualitative analysis was implemented by conducting a semi-structured interview. For the quantitative analysis, it was applied an online questionnaire to 200 participants. The results reveal that the variables used to measure brand awareness and brand image are related to each other and to purchase intention, supporting Keller’s model and suggesting that brand knowledge is related to purchase intention. The results also show that part of the participants knows the studied brand but in a superficial way.